Is Prostate Biopsy Recommended in Turkish Men with a Prostate-Specific Antigen Level between 2.5 and 4 ng/mL? - Gokhan Koc, MD; Hakan Turk, MD; Mustafa Karabicak, MD; Sitki Un, MD; Batuhan Ergani, MD; Rahmi Gokhan Ekin, MD (Elsevier, 2017)
Background: Prostate cancer is the most common solid tumor. The incidence of prostate cancer shows regional and racial differences. The ideal PSA threshold for prostate biopsy is still being debated. Objective: We aimed to investigate cancer detection rates in Turkish men who underwent transrectal ultrasound-guided prostate biopsy (TRUSPB) who had prostate-specific antigen (PSA) levels in the range of 2.5 to 4.0 ng/mL and compare them with the rates of cancer in patients with PSA levels in the range of 4.0 to 10.0 ng/mL. Methods: All Turkish men who underwent TRUSPB in our clinic between January 2012 and May 2014 were included; that is, 101 patients (Group 1) with PSA level in the range of 2.5 to 4.0 ng/mL and 522 patients (Group 2) with PSA level in the range of 4.0 to 10.0 ng/mL. Mean PSA level, age, prostate volume, and cancer detection rates were evaluated. Results: The mean age was 60.5 and 64 years in Group 1 and Group 2, respectively (P = 0.06). The mean PSA level was determined as 3.1 and 6.8 ng/mL in Group 1 and Group 2, respectively (P = 0.03). The cancer detection rate was 12.7% in Group 1 (n = 13) and 30.8% in Group 2 (n = 161), which revealed a statistically significant difference between the 2 groups (P = 0.001). In Group 1, 9 of 13 patients (69%) had Gleason score of 6, 3 (23%) had Gleason score of 7, and 1 (8%) had a Gleason score of 8. Conclusions: The cancer detection rate is lower in Turkish men with PSA level in the range of 2.5 to 4.0 ng/mL when compared with men with PSA level in the range of 4.0 to 10.0 ng/mL. Furthermore, most patients in whom cancer was detected who have a PSA level in the range of 2.5 to 4.0 ng/mL are low risk. Therefore, the benefit of TRUSBP in Turkish men with PSA level between 2.5 and 4 ng/mL is low.